The air transport system - Hirst, Mike (Woodhead, 2008)
Major operational elements of the world's air transport system are examined in this important book, which provides a rare overview and an invaluable single information source to managers in all sectors of the air transport industry. The air transport system considers route structure options in terms of operational impacts and describes the context and boundaries of the industry - the natural, regulatory and operational environments. 'Systems' perspectives are introduced to integrate the discussion of aircraft, airlines, airports and airspace issues. The issues faced in ensuring symbiosis of all these elements of the changing scene and the scope for developing balanced strategies to suit all stakeholder requirements are considered in depth to produce a comprehensive text with the potential to influence how well the air transport industry succeeds in meeting its many future challenges. Examines major operational elements of the world's air transport systemConsiders route structure options in terms of operational impactsExamines the natural, regulatory and operational boundaries of the industry.
Keywords: Aeronautics, Commercial -- Management.; Air travel -- Management.; Airlines -- Management.; Airports -- Management.; Aircraft industry.; elektronické knihy; electronic books